Computational intelligence applications for software engineering problems - Nand, Parma (Computer scientist); Nitin, Rakesh; Agrawal, Arun Prakash; Jain, Vishal, 1983- (Palm Bay, FL ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL ; Abingdon, Oxon, UK, 2023)
"This new volume explores the computational intelligence techniques necessary to carry out different software engineering tasks. Software undergoes various stages before deployment, such as requirements elicitation, software designing, software project planning, software coding, and software testing and maintenance. Every stage is bundled with a number of tasks or activities to be performed. Due to the large and complex nature of software, these tasks become more costly and error prone. This volume aims to help meet these challenges by presenting new research and practical applications in intelligent techniques in the field of software engineering. Computational Intelligence Applications for Software Engineering Problems discusses techniques and presents case studies to solve engineering challenges using machine learning, deep learning, fuzzy-logic-based computation, statistical modeling, invasive weed meta-heuristic algorithms, artificial intelligence, the DevOps model, time series forecasting models, and more. This volume will be helpful to software engineers, researchers, and faculty and advanced students working on intelligent techniques in the field of software engineering."--
A Statistical Experimentation Approach for Software Quality Management and Defect Evaluations / Alankrita Aggarwal, Kanwalvir Singh Dhindsa, and P. K. Suri -- Open Challenges in Software Measurements Using Machine Learning Techniques / Somya Goyal -- Empirical Software Engineering and Its Challenges / Sujit Kumar, Spandana Gowda, and Vikramaditya Dave -- Uncertain Multiobjective COTS Product Selection Problems for Modular Software System and Their Solutions by Genetic Algorithm / Anita R. Tailor and Jayesh M Dhodiya -- Fuzzy Logic Based Computational Technique for Analyzing Software Bug Repository / Rama Ranjan Panda and Naresh Kumar Nagwani --Software Measurements from Machine Learning to Deep Learning / Somya Goyal -- Time Series Forecasting Using ARIMA Models: A Systematic Literature Review of 2000 / Vidhi Vig -- Industry Maintenance Optimization Using AI / V. Sesha Srinivas, R. S. M. Lakshmi Patibandla, V. Lakshman Narayana, and B. Tarakeswara Rao -- Comparative Study of Invasive Weed Optimization Algorithms / Shweta Shrivastava, D. K. Mishra, and Vikas Shinde -- An Overview of Computational Tools / Navneet Kaur, Shalini Sahay, and Shruti K. Dixit -- Enhanced Intelligence Architecture / N. Ambika -- Systematic Literature Review of Search-Based Software Engineering Techniques for Code Modularization/Remodularization / Divya Sharma and Ganga Sharma -- Automation of Framework Using DevOps Model to Deliver DDE Software / Ishwarappa Kalbandi and Mohana.
OCLC-licensed vendor bibliographic record.
Keywords: Software engineering; Computational intelligence; COMPUTERS / Computer Science; COMPUTERS / Programming / Software Development